Cyclometallated Iridium-PhanePhos Complexes Are Active Catalysts in Enantioselective Allene-Fluoral Reductive Coupling and Related Alcohol-Mediated Carbonyl Additions that Form Acyclic Quaternary Carbon Stereocenters - Schwartz, Leyah A. (J Am Chem Soc, 2019)
Iridium complexes modified by PhanePhos catalyze the 2-propanol-mediated reductive coupling of diverse 1,1-disubstituted allenes 1a-1u with fluoral hydrate 2a to form CF(3)-substituted secondary alcohols 3a-3u that incorporate acyclic quaternary carbon-containing stereodiads. By exploiting concentration-dependent stereoselectivity effects related to the interconversion of kinetic (Z)- and thermodynamic (E)-σ-allyliridium isomers, adducts 3a-3u are formed with complete levels of branched regioselectivity and high levels of anti-diastereo- and enantioselectivity. The utility of this method for construction of CF(3)-oxetanes and CF(3)-azetidines is illustrated by the formation of 4a and 6a, respectively. Studies of the reaction mechanism aimed at illuminating the singular effectiveness of PhanePhos as a supporting ligand in this and related transformations have led to the identification of a chromatographically stable cyclometallated iridium-(R)-PhanePhos complex Ir-PP-I that is catalytically competent for allene-fluoral reductive coupling and previously reported transfer hydrogenative C-C couplings of dienes or CF(3)-allenes with methanol. Deuterium labelling studies, reaction progress kinetic analysis (RPKA) and computational studies corroborate a catalytic mechanism involving rapid allene hydrometalation followed by turnover-limiting carbonyl addition. A computationally determined stereochemical model shows the ortho-CH(2) group of the cyclometallated iridium-PhanePhos complex plays a key role in directing diastereo- and enantioselectivity. The collective data provide key insights into the structural-interactional features of allyliridium complexes required to enforce nucleophilic character, which should inform the design of related cyclometallated catalysts for umpoled allylation.